An Icon Design Approach Based on Symbolic and Users' Cognitive Psychology - Sun Qiang; Hu Fei (Indonesian Journal of Electrical Engineering and Computer Science, 2016)
In order to explore the usability and ease of use of icon design, the icon design method based on the combination of semiotics and user cognitive psychology is raised. Based on the principle of matching the icon design knowledge and user knowledge, the icon design process is analyzed from four dimensions, namely the semantic expression of elements, the structure of elements, the interface and cultural context, and the user cognitive characteristics. An icon assistant design system CDIPV1.0 is structured, it can realize knowledge sharing, rapid icon designing, and professional evaluation based on the combination of semiotics and users’ cognitive psychology. The theory is verified through it.